THE CHARACTERISATIONS OF PISCINE MOLITOR PATEL IN YAN MARTELL’S THE LIFE OF PI - Suwastini, Ni Komang Arie; Asri, Ni Wayan Desy Prema; Wahyuni, Luh Gede Eka; Prastika, Kadek Ayu Dewi (Universitas Pendidikan Ganesha, 2020)
Literature like novels can contain many moral teachings, including how a human being develops into a better person because of certain events experienced during the plot development. The present study focuses on the character development of Piscine Molitor Patel in Yan Martell's The Life of Pi as he had to survive the Pacific Ocean for 227 days on a lifeboat with a hungry tiger. By employing close reading, it is revealed that Piscine Molitor Patel was revealed as a curious, smart, competitive, empathetic, obedient, loving, and humble character. These characterizations were revealed directly through the author's description and indirectly through thought, speech, and action. From these character revelations, it can be concluded that the development of Pi’s curious, smart, competitive, empathetic, obedient, loving, and humble character had help Pi survive the Pacific Ocean and continued living as a better person. By employing Freud’s psychoanalysis, Pi’s characterizations were then classified as reflections of his id, ego, and superego. The present study concludes that Pi’s characterizations reflect the development of the balance between his id, ego, and superego, which allowed him to survive the shipwreck and grow into a better person.